Autoinflammatorische Erkrankungen als Differenzialdiagnose des Fiebers unklarer Genese - Kümmerle-Deschner, Jasmin Beate (DMW - Deutsche Medizinische Wochenschrift, 2017)
Fever is the most leading symptom of autoinflammatory diseases (AID). Therefore, AID have to be considered in differential diagnosis concerning fever of unknown origin. Unspecific Inflammatory manifestations may lead to misinterpretations that possibly cause irreversible organ damage. Effective treatment options are available and imply profound diagnostics.
Keywords: Fieber; autoinflammatorische Erkrankungen; Genetik; Colchicin; Interleukin-1-Inhibitoren